Features of determination of the efficiency of devices for improvement of ecological safety level of vehicles with reciprocating ICE exploitation - Kondratenko, Olexandr Mykolayovych; Chernobay, Gennadiy Olexandrovych; Derkach, Juriy Fedorovych; Kovalenko, Svitlana Andriivna (Національний технічний університет "Харківський політехнічний інститут", 2019)
This article describes the results of analysis and numerical study of prof. I.V. Parsadanov conversion formula as the one of relevant issues of the metrological features of determination of particulate matter mass hourly emission in exhaust gases flow of reciprocating internal combustion engine on the testing bench without dilution tunnel. Purpose of the study is detection of relationship between magnitudes of cleaning efficiency coefficients of particulate matter filter of diesel reciprocating internal combustion engine for unburned hydrocarbons volume concentration in exhaust gas flow and emission of particulate matters with using of conversion formula for whole dia pason of changing of influencing factors. Object of the study is efficiency of operation of system of neutralization of legislative normalized pollutants in diesel internal combustion engine exhaust gases flow, namely particulate matter filter. Subject of the study is relationship between magnitudes of indicators that characterized object of the study which connected with each other by conversion formula. It was showed that the magnitudes of values of efficiency coefficients of operation of particulate matter filter of diesel reciprocating internal combustion engine for indicators of opacity and concentration of unburned hydrocarbons in exhaust gas which was obtained by direct measurements during bench motor tests and also mass hourly emission of particulate matter in exhaust gas flow which was obtained with using of the conversion formula, is not equal to each other for every individual operational regime of diesel engine.Calculation assessment and graphical illustration of relationship between magnitudes of this coefficients for unburned hydrocarbons volume concentration in exhaust gas flow and emission of particulate matter for whole diapason of changing of influencing factors was carried out. For the first time it was detected the differences between magnitudes of values of efficiency coefficients of particulate matter filter operation process of diesel internal combustion engine in pairs for mass hourly particulate matter emission with exhaust gases flow and opacity and toxicity of exhaust gases which connected with each other by conversion formula.

Проаналізовано і розрахунково досліджено формулу перерахунку проф. І.В. Парсаданова як одного з актуальних питань метрологічних особливостей процесу отримання значень масового годинного викиду твердих частинок поршневого двигуна внутрішнього згоряння на моторному випробувальному стенді, не обладнаному тунелем розведення. Метою дослідження є виявлення співвідношення значень коефіцієнтів ефективності роботи фільтра твердих частинок дизе-льного поршневого двигуна внутрішнього згоряння за викидами твердих частинок та концентрацією незгорілих вуглеводнів у відпрацьованих газах із застосуванням формули перерахунку для всього діапазону зміни значень впливаючих факторів. Об’єктом дослідження є ефективність функціонування системи нейтралізації законодавчо нормованих полютантів потоці відпрацьованих газів дизельного двигуна внутрішнього згоряння, а саме фільтра твердих частинок. Предметом дослідження є взаємозв’язок між значеннями показників, які характеризують об’єкт дослідження, пов’язані між собою формулою перерахунку. Показано, що значення коефіцієнтів ефективності роботи фільтра твердих частинок дизельного двигуна внутрішнього згоряння за показниками димності й концентрації незгорілих вуглеводнів у відпрацьованих газах, отримані прямими вимірюваннями у ході стендових моторних випробувань, а також масового годинного викиду твердих частинок з потоком відпрацьованих газів, отримані за вказаною формулою перерахунку, не збігаються для кожного стаціонарного режиму його роботи. Розрахунково оцінено та проілюстровано графічно співвідношення значень цих коефіцієнтів за концентрацією незгорілих вуглеводнів у відпрацьованих газах і викидом твердих частинок для всього діапазону зміни впливаючих факторів. Вперше виявлено різницю між значеннями величин коефіцієнтів ефектив-ності роботи фільтра твердих частинок дизельного двигуна внутрішнього згоряння попарно для масового годинного викиду твердих частинок з потоком відпрацьованих газів та димності й токсичності відпрацьованих газів, що пов’язані між собою формулою перерахунку.
Особливості визначення ефективності пристроїв для покращення рівня екологічної безпеки експлуатації транспортних засобів з поршневим ДВЗ
Keywords: environment protection technologies; ecological safety; power plants; particulate matter emission; технології захисту навколишнього середовища; екологічна безпека; енергетичні установки; викид твердих частинок